A new species of Lachesilla in species group pedicularia (Psocodea: ‘Psocoptera’: Lachesillidae) and a new record of L. aethiopica (Enderlein) from India - Ramesh, Gurusamy; Babu, Rajappa; Subramanian, Kumarapuram A.; Neri, García Aldrete Alfonso (Zootaxa, 2021)
Species of Lachesilla Westwood, in which the males have one clunial apophysis are so far known only in the Neotropics. We here describe a species of Lachesilla in the pedicularia species group from the Southern Western Ghats, India. The males present a short, distally obtusely concave apophysis in the clunium, over the area of the epiproct. Lachesilla aethiopica (Enderlein) known in the Neotropics, the USA and Africa, was collected in Tamil Nadu, India, representing a range extension to Asia.